Volumetric B1+ Mapping of the Brain at 7T using DREAM. Issue 1 (14th February 2013) - Nehrke, Kay; Versluis, Maarten J.; Webb, Andrew; Börnert, Peter
<x xml:space="preserve">Abstract</x> Purpose To tailor and optimize the Dual Refocusing Echo Acquisition Mode (DREAM) approach for volumetric B1+ mapping of the brain at 7T. Theory and Methods A new DREAM echo timing scheme based on the virtual stimulated echo was derived to minimize potential effects of transverse relaxation. Furthermore, the DREAM B1+ mapping performance was investigated in simulations and experimentally in phantoms and volunteers for volumetric applications, studying and optimizing the accuracy of the sequence with respect to saturation effects, slice profile imperfections, and T1 and T2 relaxation. Volumetric brain protocols were compiled for different isotropic resolutions (5–2.5 mm) and SENSE factors, and were studied in vivo for different RF drive modes (circular/linear polarization) and the application of dielectric pads. Results Volumetric B1+ maps with good SNR at 2.5 mm isotropic resolution were acquired in about 20 s or less. The specific absorption rate was well below the safety limits for all scans. Mild flow artefacts were observed in the large vessels. Moreover, a slight contrast in the ventricle was observed in the B1+ maps, which could be attributed to T1 and T2 relaxation effects. Conclusion DREAM enables safe, very fast, and robust volumetric B1+ mapping of the brain at ultrahigh fields. Magn Reson Med 71:246–256, 2014. © 2013 Wiley Periodicals, Inc.